Frequency and Risk Factors for Hyperglycemia in Children with Acute Lymphoblastic Leukemia During Induction Chemotherapy (Bangladesh Journal of Child Health, 2022)
Background: Hyperglycemia is a common side effect and it has long been recognized as a consequence of corticosteroids and L-asparaginase, chemotherapeutic agents key to ALL treatment. This study was done to determine the frequency and identify the risk factors for hyperglycemia in paediatric ALL during induction chemotherapy.Material & Methods: This prospective observational study was done among 87 newly diagnosed ALL cases of 1-18 years of age. After initial work up patient got induction chemotherapy according to UK ALL 2003 (modified) protocol in BSMMU. Anthropometric measurements and CBC, RBS/ 2 hours after glucose/ FBS and corresponding urine sugar was assessed after 2nd, 4th, 6th and 9th dose of Lasparaginase and after completion of induction. Data were analyzed by SPSS 17.0.Results: Eight patients (9.75%) of the study cohort developed hyperglycemia. Among ³10 years of age 36.8% had hyperglycemia compared to 1.6% of younger children (p